The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijms22115601
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Aptamer-Mediated Liquid Biopsy for Early Detection of Cancer

Abstract: The early detection of cancer favors a greater chance of curative treatment and long-term survival. Exciting new technologies have been developed that can help to catch the disease early. Liquid biopsy is a promising non-invasive tool to detect cancer, even at an early stage, as well as to continuously monitor disease progression and treatment efficacy. Various methods have been implemented to isolate and purify bio-analytes in liquid biopsy specimens. Aptamers are short oligonucleotides consisting of either D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 173 publications
0
20
0
1
Order By: Relevance
“…Besides being a potential strategy for cancer therapy, the use of oligonucleotides holds promise for treating also many forms of illness due to genetic aberrations (for example, neurological and ocular diseases). They also deserve to be used clinically in diagnostic procedures, such as liquid biopsy [ 28 , 29 , 30 ]. Safety may be a major concern for this type of molecule, along with a lack of efficacy, potentially due to difficulty in delivering the active components to the site of action.…”
Section: Genetic Therapy For Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being a potential strategy for cancer therapy, the use of oligonucleotides holds promise for treating also many forms of illness due to genetic aberrations (for example, neurological and ocular diseases). They also deserve to be used clinically in diagnostic procedures, such as liquid biopsy [ 28 , 29 , 30 ]. Safety may be a major concern for this type of molecule, along with a lack of efficacy, potentially due to difficulty in delivering the active components to the site of action.…”
Section: Genetic Therapy For Cancermentioning
confidence: 99%
“…Our experience with vaccines to prevent SARS-CoV-2 infection at an international level shows that they have a highly favorable safety profile, with some rare fatal events, considering the vast number of people vaccinated worldwide in the post-marketing setting. It must be highlighted that the biopharmaceutical technology that led, in a very short time, to the development of COVID vaccines (i.e., mRNA vaccines) comes from cancer immunotherapy research [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Commonly detected toxic responses following cancer vaccine administration include myalgia, cough, chills, fever, pain at the injection site, asthenia, flu-like syndrome, and respiratory abnormalities [ 20 ,…”
Section: Pharmacovigilance and Adverse Drug Reactions (Adrs) Of Genet...mentioning
confidence: 99%
“…19 The results of recent studies on CTCs or circulating nucleic acids have demonstrated that liquid biopsy has a good capacity for the early detection of cancer, including recurrence after treatment. [20][21][22][23] Additionally, emerging biomarkers found to be closely correlated with some diseases show great potential in indicating prognosis and deciding appropriate therapies for patients. 24,25 Another advantage of liquid biopsy compared to traditional surgical resection is the continuous acquisition of specimens, which renders it an ideal approach for patient follow-up and treatment response monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The noninvasiveness and easy handling of liquid biopsy samples enable diagnosis, especially for inoperable patients 19 . The results of recent studies on CTCs or circulating nucleic acids have demonstrated that liquid biopsy has a good capacity for the early detection of cancer, including recurrence after treatment 20–23 . Additionally, emerging biomarkers found to be closely correlated with some diseases show great potential in indicating prognosis and deciding appropriate therapies for patients 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Various biological fluids including peripheral blood, urine, pleural fluid, ascites, seminal fluid, and cerebrospinal fluid (CSF) are used to isolate circulating targets for diagnostic applications. However, it is difficult to preserve the biological functions and viability of analytes isolated from liquid biopsy samples, and the reliability of the targets chosen by the analyte is not yet clear [8]. Liquid biopsies could be used as an alternative to tumor biopsies to evaluate predictive biomarkers and responses to therapy, and there are many new studies evaluating the clinical effects of this new technique.…”
Section: Introductionmentioning
confidence: 99%